Evidence-based case report: effects of exercise-based cardiac rehabilitation in repaired tetralogy of Fallot - Salam, Muhamad Elfitra; Putra, Bima Lesmana (P3M Universitas 'Aisyiyah Surakarta, 2025)
Background: Several sequelae may persist following corrective surgery for tetralogy of Fallot (ToF), including reduced exercise capacity, compromised vascular and cardiac autonomic function, and diminished quality of life. While exercise-based cardiac rehabilitation is commonly implemented for patients with congenital heart disease, there remains a lack of comprehensive understanding regarding the optimal frequency, intensity, duration, and type of exercise. This evidence-based case report aims to evaluate the effectiveness of physical exercise on exercise capacity and quality of life in patients who have undergone ToF repair. Method: A literature search was conducted in PubMed, Cochrane, and Google Scholar databases in September to December 2024 using keywords